Effect of Helicobacter pylori Eradication on TLR2 and TLR4 Expression in Patients with Gastric Lesions - Aline Cristina Targa Cadamuro; Ana Flávia Teixeira Rossi; Joice Matos Biselli-Périco; Patrícia Fucuta Pereira; Edla Polsinelli Bedin Mascarin Do Vale; Ricardo Acayaba; Kátia Ramos Moreira Leite; Eny Maria Goloni-Bertollo; Ana Elizabete Silva (Hindawi Limited, 2015)
Objective. Helicobacter pylori (Hp) is recognized by TLR4 and TLR2 receptors, which trigger the activation of genes involved in the host immune response. Thus, we evaluated the effect of eradication therapy on TLR2 and TLR4 mRNA and protein expression in H. pylori-infected chronic gastritis patients (CG-Hp+) and 3 months after treatment. Methods. A total of 37 patients CG-Hp+ were evaluated. The relative quantification (RQ) of mRNA was assessed by TaqMan assay and protein expression by immunohistochemistry. Results. Before treatment both TLR2 and TLR4 mRNA in CG-Hp+ patients were slightly increased (TLR2 = 1.32; TLR4 = 1.26) in relation to Hp-negative normal gastric mucosa (P≤0.05). After successful eradication therapy no significant change was observed (TLR2 = 1.47; TLR4 = 1.53; P>0.05). In addition, the cagA and vacA bacterial genotypes did not influence the gene expression levels, and we observed a positive correlation between the RQ values of TLR2 and TLR4, both before and after treatment. Immunoexpression of the TLR2 and TLR4 proteins confirmed the gene expression results. Conclusion. In conclusion, the expression of both TLR2 and TLR4 is increased in CG-Hp+ patients regardless of cagA and vacA status and this expression pattern is not significantly changed after eradication of bacteria, at least for the short period of time evaluated.